2013
DOI: 10.2516/ogst/2013143
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Conditions and SGS Models for LES of Wall-Bounded Separated Flows: An Application to Engine-Like Geometries

Abstract: and available online here Cet article fait partie du dossier thématique ci-dessous publié dans la revue OGST, Vol. 69, n°1, et téléchargeable ici D o s s i e rDOSSIER Edited by/Sous la direction de : C. Angelberger IFP Energies nouvelles International Conference / Les Rencontres Scientifiques d'IFP Energies nouvelles LES4ICE 2012 -Large Eddy Simulation for Internal Combustion Engine FlowsLES4ICE 2012 -La simulation aux grandes échelles pour les écoulements dans les moteurs à combustion interne Oil & Gas Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…It was found that LSR provides a more precise estimation of the local grid resolution and may provide hints about the overall simulation quality [22,23]. Experience showed that LSR ≤ 5 can be used as a quality threshold to assess local mesh resolution.…”
Section: Averaged Fieldsmentioning
confidence: 95%
See 2 more Smart Citations
“…It was found that LSR provides a more precise estimation of the local grid resolution and may provide hints about the overall simulation quality [22,23]. Experience showed that LSR ≤ 5 can be used as a quality threshold to assess local mesh resolution.…”
Section: Averaged Fieldsmentioning
confidence: 95%
“…LES was performed using the finite volume CFD code OpenFOAM [31], which was extended for this work by the WALE subgrid scale (SGS) model in its compressible formu- [23] and by an improved mesh motion strategy, which is particularly suitable for IC engines [14,21].…”
Section: Large Eddy Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several efforts have been devoted to implement solution-adaptive gridding methodology (Pope, 2004;Celik et al, 2005;Brusiani and Bianchi, 2008;Davidson, 2009;Piscaglia et al, 2014;Xiao et al, 2014), however, here we only undertook an assessment of the results quality after the grid was prescribed.…”
Section: Assessment Of Les Results Qualitymentioning
confidence: 99%
“…In spite of its relative simplicity, this case is quite popular among engine CFD modelers [7,[10][11][12][39][40][41], because of its close resemblance to an actual engine intake flow. Figure 2a sketches the domain configuration, while Table 2 contains the dimensional parameters and flow conditions used for the simulations' setup.…”
Section: Fixed Intake Valvementioning
confidence: 99%